THE URGENCY OF MORTGAGE AGREEMENT AS AN EFFORT TO REALIZE THE TRUST BY BANK AS CREDITOR - Atikah, Ika (Jurnal Hukum dan Peradilan, 2021)
This study focuses on the legal certainty of the implementation of loans for mortgage rights which are the object of collateral in the form of money-valued objects when bad loan occurs, which are regulated in the main agreement as an effort to manifest the trust of creditors of banking institutions whose existence is highly sought after by the Indonesian people. The method used in this study focuses on the normative with the conceptual approach and statute approach. The results of this study indicate that Credit agreements must be considered by the bank as creditor and by the customer as the debtor, considering that credit agreements have a vital function in granting, managing, and managing the credit itself. The existence of a guarantee in a bank credit agreement is significant, namely as a means of legal protection for bank security in overcoming risks. There is a certainty that the debtor customer will pay off his loan. This is based on the explanation of Banking Laws, PBI, and POJK, which requires banks' caution as creditors for loans to debtors based on the belief in the debtor's ability to pay off his obligations as agreed in the agreement. The land is material security which is most in demand by banking institutions as security of mortgage rights. The use of land as a trusted and consumptive credit is based on the consideration of the safest land and has a relatively high sale value. The urgency of objects Securing mortgage rights as stipulated in the credit agreement cannot be separated from the guarantee itself. Credit guarantees are always stated in an additional agreement, namely the Collateral agreement. The need for funds by people or institutions provides credit by providing excellent services and providing legal protection for the parties in the transaction so that no one is harmed in the transaction. The state provides legal protection by stipulating legal regulation relating to credit so that banks as creditors have legal certainty in the process of executing credit collateral objects for optimal repayment. Mortgage Law states that creditors have full rights in executing debtor's collateral goods when bad loans do not have to go through litigation.